Placenta percreta causing spontaneous uterine rupture and intrauterine fetal death in an unscared uterus: A case report. (2019) - Enebe, J.T.; Ofor, I.J.; Okafor, I.I.
Highlights: Placenta percreta causing hemoperitoneum and intrauterine death can easily be misdiagnosed. Uterine rupture is rare in unscarred uterus and in absence of trauma. Placenta percreta is an unusual cause of uterine rupture. Placental percreta is an unusual cause of heamoperitoneum and intra-uterine death. Abstract: Introduction: Placenta percreta is a rare; a life-threatening disorder of placentation and one of the components of the placenta accreta spectrum. It can lead to uterine rupture, an obstetric catastrophe that can be associated with increased maternal and fetal morbidity and mortality. Presentation of case: We present an unusual case of spontaneous uterine rupture due to placenta percreta in an unscarred uterus of a multiparous woman leading to spontaneous intrauterine fetal death. She presented with hypovolaemic shock following spontaneous rupture of the uterus and subsequent intra-peritoneal bleeding. Discussion: Uterine rupture occurs commonly in a scarred uterus from some form of trauma or injudicious use of oxytocics. However, uterine rupture occurring in the absence of prior scar or use of oxytocics is a rarity. Placenta percreta is an unusual cause of uterine rupture and subsequent intra-uterine fetal death. Placenta percreta occurs when the uterine wall is invaded by the placenta up to the level of the serosa. A high index of suspicion and thorough review of the patient is required for making this diagnosis. Misdiagnosis is associated with dare consequences of increased maternal morbidity and mortality. Conclusion: Placenta percreta is a rare disorder of placentation that can cause uterine rupture which can easily be misdiagnosed. Prompt diagnosis and institution of the appropriate care can help prevent catastrophic outcomes as demonstrated in the case reported.